Prevention of The Crime Of Trafficking in Persons (TPPO) in Cases Of Illegal Sending Indonesian Migrant Workers (PPMI) Overseas as Foreign Ship Crew - Aulia, Aulia (RechtIdee, 2024)
Human trafficking is a transnational crime in the form of human smuggling and is the third largest transnational crime in the world after drugs and weapons. Some of the contributing factors are cheap labor, low risk, high reward, and sexual demands. From 2017 World Bank data, there are 9 million Indonesians working abroad and only 4.7 million are recorded in SISKOP2MI (Indonesian Migrant Worker Protection Computer System), the remaining 4.3 million people are illegal. This is the background to which this research was conducted. It is not easy to prevent and eradicate criminal acts of trafficking in persons (TPPO) because it requires the seriousness of many parties, from the police, courts, public prosecutors to the Ministry. Human trafficking has various modes, apart from the perpetrators and victims, it must always be understood in terms of legal definitions. Without theoretical guidelines and legal norms, it would be dangerous because it could lead to wrong shots, for example in determining a suspect. This research uses secondary legal materials, a case approach and uses prescriptive analysis. It is hoped that the results of this analysis can provide input for efforts to prevent and eradicate TIP in the jurisdiction of each Regional Police/Polres.